An investigation on the effects of source of funding on the provision of water and sewerage services: a case of city of Gweru - Ezra, Solomon (Midlands State University, 2019)
Provision of water and sewerage system has been a problem in many cities in most developing countries and this has resulted in many residents being exposed to water borne diseases. In Zimbabwe many Local Authorities are struggling to efficiently provide water and sewer services. There are so many factors that can be linked to the challenges faced by local authority in the provision of water and sewerage system among them being source of funding. This project sought to investigate the impact of source of funding on the provision of water and sewer services in local authorities focusing on City of Gweru. This is against the background that some locations in the City do not receive water supply timeously and that there are dotted burst sewer pipes in the City that is threatening health of the residents. The researcher used descriptive was collected through descriptive design and primary data was also collected through interviews as well as questionnaires. Population samples were drawn from management as well as Gweru Residents Association as they have relevant information patterning to service delivery as well as funding. This paper showed that poor service delivery was caused by funding, but there are also other factors that contributed to poor service such as poor management, lack technical expertise, and diverting funds for other uses also affected service delivery for water and sewer. Based on the findings the researcher recommended that a water and sewer Engineer be recruited to come up with framework in the development and maintenance of the sewer system infrastructure.